Connection between Relationship Quality and Megaproject Success: Moderating Role of Contractual Functions - Dedong Wang; Yongqiang Lu; Shaoze Fang (Advances in Civil Engineering)
Relational governance is critical to project success. The present study on relational governance fails to elaborate on the relation between relationship quality and project success. In line with social exchange theory, this paper presents an empirical research of Chinese megaprojects to explore the effect of social exchange factors on relationship quality. Particularly, this research investigated how mianzi (face) as a factor variable affects relationship quality in megaprojects. This work also divided contract functions into control, coordination, and adaptation to investigate the impact of these functions on the relationship between social exchange factors and mianzi (face) with relationship quality. Results corroborate the following points: (1) relationship quality has a significant effect on project success; (2) relationship quality is also significantly influenced by trust, reciprocity, commitment, and mianzi; and (3) regarding the moderating effects of contractual functions, the contractual control function has a positive influence on the relationship between trust, commitment, and relationship quality and has a negative influence on the relationship between mianzi and relationship quality. However, contractual control has no apparent effect on the relationship between reciprocity and relationship quality. The contractual coordination function has a positive effect on the relationship between trust, commitment, and relationship quality. The contractual adaptation function has a significant positive effect on the relationship between trust and relationship quality. These findings provide new insights into relationship governance, and suggestions for contractual function design are provided.